2016
DOI: 10.1111/gcb.13493
|View full text |Cite
|
Sign up to set email alerts
|

Press–pulse interactions: effects of warming, N deposition, altered winter precipitation, and fire on desert grassland community structure and dynamics

Abstract: Global environmental change is altering temperature, precipitation patterns, resource availability, and disturbance regimes. Theory predicts that ecological presses will interact with pulse events to alter ecosystem structure and function. In 2006, we established a long-term, multifactor global change experiment to determine the interactive effects of nighttime warming, increased atmospheric nitrogen (N) deposition, and increased winter precipitation on plant community structure and aboveground net primary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 93 publications
0
37
2
1
Order By: Relevance
“…However, though warming negatively affected soil moisture ( Figure 6), warming did not significantly decreased community ANPP in our study. This contrasts with the results of many other studies in which warming either increased (Collins et al, ;Cowles, Wragg, Wright, Powers, & Tilman, 2016;Wu, Dijkstra, Koch, Peñuelas, & Hungate, 2011) or decreased (Rustad et al, 2001) aboveground plant biomass. Similar to the warming effect, precipitation reduction also decreased soil moisture but did not change community ANPP, which was again different from results from most previous studies (Hoover, Knapp, & Smith, 2014;Reichmann & Peters, 2013).…”
Section: Aboveground Net Primary Productivity Responds To Warming Acontrasting
confidence: 99%
See 1 more Smart Citation
“…However, though warming negatively affected soil moisture ( Figure 6), warming did not significantly decreased community ANPP in our study. This contrasts with the results of many other studies in which warming either increased (Collins et al, ;Cowles, Wragg, Wright, Powers, & Tilman, 2016;Wu, Dijkstra, Koch, Peñuelas, & Hungate, 2011) or decreased (Rustad et al, 2001) aboveground plant biomass. Similar to the warming effect, precipitation reduction also decreased soil moisture but did not change community ANPP, which was again different from results from most previous studies (Hoover, Knapp, & Smith, 2014;Reichmann & Peters, 2013).…”
Section: Aboveground Net Primary Productivity Responds To Warming Acontrasting
confidence: 99%
“…In a previous study, Zavaleta, Shaw, Chiariello, Mooney, and Field () reported that global changes affected plant species richness primarily driven by changes in forbs richness. Collins et al () found that warming significantly increased biomass of forbs after a wildfire. These results, together with our findings, suggested that forbs were likely to be highly sensitive to environmental changes and were decreased primarily by drought.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the idea that multiple perturbations are more likely to result in state changes (Paine et al., ). For instance, wildfire in the Chihuahuan desert altered the response to ongoing experimental warming and precipitation manipulations (Collins et al., ) and following experimental warming in shrublands across Europe, recently disturbed areas experienced greater vegetation loss than undisturbed areas (Kröel‐Dulay et al., ). Similar synergistic relationships between climate extremes and disturbance have been proposed for ecosystems ranging from semi‐arid woodlands (Allen & Breshears, ) to tropical forests (Brando et al., ; Staal et al., ) and coral reefs (Mumby, Wolff, Bozec, Chollett, & Halloran, ).…”
Section: Discussionmentioning
confidence: 99%
“…Winter climate is influential in many ecosystems (Ladwig et al., ) and experimental manipulations help examine the response of ecological systems to changing winter conditions (Kreyling, ). Snow manipulations test for the ecological consequences of altered winter precipitation (Kreyling, Haei, & Laudon, ; Loik, Griffith, & Alpert, ), and warming manipulations track ecosystem changes following gradual increases in temperature (Collins et al., ; Wu, Dijkstra, Koch, Penuelas, & Hungate, ), yet our understanding of the response of plant communities to winter climate extremes is often limited to opportunistic studies following extreme climate events, as large‐scale cooling experiments are generally not practical. For example, ice storms in hardwood forests can temporarily increase canopy openness and shift community composition based on species shade tolerance (Arii & Lechowicz, ; Rhoads et al., ; Shao, Huang, Liu, Kuang, & Li, ; Weeks, Hamburg, & Vadeboncoeur, ).…”
Section: Introductionmentioning
confidence: 99%